Dampak tingkat konsentrasi dan profitabilitas terhadap persaingan bank konvensional di indonesia - Wulandary, Renny (JURNAL MANAJEMEN, 2016)
This study examines the relationship between concentration, profitability and conventional commercial banks competition in Indonesia from 2009 to 2013. The sampling method used by this research is purposive sampling method. By following the criteria in this method, the number of sample is 109 banks. A simple regression model is used to analize the data. This research used secondary data from Bank Indonesia and the level of concentration and profitability are represented by HHI (Herfindahl-Hirschman Index) and ROA (Return on Assets), respectively. Panzar and Rosse is employed to measure competition. The results of study show the relationship between concentration level and competition is negatively significant, whilst the profitability affect negatively on competition but statistically insignificant.Keyword: Concentration, profitability, competition, conventional commercial Bank